ASSESSMENT EFFECTIVENESS ANALYSIS SYSTEM USING G-FORM WITH TAM METHOD AT SD GALATIA3 JAKARTA BARAT - Asrul Sani; Agus Budiyantara; Rizaldy Khair; Siti Aisyah (Kresnamedia Publisher, 2022)
Students feel the impact of the spread of Covid-19, such as changes in the provision of services in educational institutions, such as formal education at all levels, non-formal education, to academics. The government began to implement an online learning system (online). The problem during this online learning period is that many people are still not ready to face technology, both teachers and students. It happened in the early days of the pandemic. It results in challenges for the standard learning process, including challenges for teaching and giving assessments. It is because the teaching staff (teachers) always have daily assessment data that is usually carried out daily during everyday learning. However, during this PJJ period, teachers became confused about giving daily assessments to their students. The research aims to analyze and evaluate the online learning system using a platform that is easy to operate by teachers and can be accessed anywhere, namely Google Forms. In the Google Form application, there is an automatic calculation system in the form of student feedback where teachers do not bother to manually calculate the results of student learning evaluations. The analysis method used is the Technology Acceptance Model (TAM), which can determine users' attitudes towards the technology used, so that teachers can easily find out whether the tasks given to students are done by the students themselves, not with the help of parents.